Conformational surveillance of Orai1 by a rhomboid intramembrane protease prevents inappropriate CRAC channel activation - Grieve, Adam G; Yeh, Yi-Chun; Chang, Yu-Fen; Huang, Hsin-Yi; Zarcone, Lucrezia; Breuning, Johannes; Johnson, Nicholas; Stříšovský, Kvido; Brown, Marion H; Parekh, Anant B; Freeman, Matthew (Molecular cell, 2021)
Calcium influx through plasma membrane calcium release-activated calcium (CRAC) channels, which are formed of hexamers of Orai1, is a potent trigger for many important biological processes, most notably in T cell-mediated immunity. Through a bioinformatics-led cell biological screen, we have identified Orai1 as a substrate for the rhomboid intramembrane protease RHBDL2. We show that RHBDL2 prevents stochastic calcium signaling in unstimulated cells through conformational surveillance and cleavage of inappropriately activated Orai1. A conserved disease-linked proline residue is responsible for RHBDL2's recognizing the active conformation of Orai1, which is required to sharpen switch-like signaling triggered by store-operated calcium entry. Loss of RHBDL2 control of CRAC channel activity causes severe dysregulation of downstream CRAC channel effectors, including transcription factor activation, inflammatory cytokine expression, and T cell activation. We propose that this surveillance function may represent an ancient activity of rhomboid proteases in degrading unwanted signaling proteins.
Keywords: Protein Binding; Drosophila melanogaster; Ion Channel Gating; protein ORAI1; Calcium; stochastické procesy; mutace; rhomboid protease; HEK293 buňky; Calcium Signaling; Peptide Hydrolases; Orai1; výpočetní biologie; vápník; membránové proteiny; gating iontového kanálu; signální transdukce; Lymphocyte Activation; Membrane Proteins; CRAC channel; HEK293 Cells; signalling; Signal Transduction; aktivace lymfocytů; T cell; calcium; vazba proteinů; Cell Membrane; RHBDL2; vápníková signalizace; Animals; lidé; ORAI1 Protein; Serine Endopeptidases; konformace proteinů; Stochastic Processes; Humans; zvířata; transmembrane; serinové endopeptidasy; buněčná membrána; Calcium Channels; Protein Conformation; Mutation; proteasy; Computational Biology; vápníkové kanály